Integration von Nachhaltigkeitsaspekten in die operativen und strategischen Prozesse von Kapitalverwaltungsgesellschaften für Immobilienfonds - Friedrich, Thomas (Karlsruher Schriften zur Bau-, Wohnungs- und Immobilienwirtschaft, 2022)
In this work, a proposal for the integration of sustainability aspects into existing risk and portfolio management processes of capital management companies for real estate funds is developed and presented. Here, the technical test criteria for the construction and renovation, acquisition and ownership of real estate originating from the current EU regulation on taxonomy were taken up and transferred to a test scheme.